2008
DOI: 10.2137/1239099043633350
|View full text |Cite
|
Sign up to set email alerts
|

Coefficients of relationship and inbreeding among Finnish Ayrshire and Holstein-Friesian

Abstract: Pedigree data from national breeding value evaluations were used in calculation of the coeffi cient and rate of inbreeding, average coeffi cient and rate of relationship and generation intervals for the Finnish Ayrshire and Holstein-Friesian dairy cattle populations. The data had 1,366,555 Ayrshire and 377,869 Holstein-Friesian animals. The mean coeffi cient of inbreeding for Ayrshire and Holstein-Friesian animals born in the 1990s was 2.29% and 0.90%, respectively, and the trend was towards higher inbreeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, genetic variation will ensure a capacity for long-term response to selection pressures, either through artificial or natural selection (Frankham, Ballou and Briscoe, 2002). Additionally, Vahlsten, Mäntysaari and Strandén (2004) emphasized the importance of monitoring the level and rate of inbreeding within a population across time. The reduction of genetic variability in beef cattle has been researched extensively (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genetic variation will ensure a capacity for long-term response to selection pressures, either through artificial or natural selection (Frankham, Ballou and Briscoe, 2002). Additionally, Vahlsten, Mäntysaari and Strandén (2004) emphasized the importance of monitoring the level and rate of inbreeding within a population across time. The reduction of genetic variability in beef cattle has been researched extensively (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The additive relationship values of each of the selected tails, for each trait, were very similar to each other's, ranging from 4.26 to 4.37 %; but they were higher than the corresponding value calculated for the whole population (3.01%). To appraise the extent of the difference in the average relationship between the tails and the whole population, it is useful to cite Vahlsten et al [ 16 ] who reported that an increase by 0.96 % units of relationship, per generation, is to be considered slow, this value referring to Friesian bulls, born during 40 years, and belonging to a population of over 400,000 animals. It can therefore be inferred that the relationship differences observed in the present study reproduce the mere generational trend.…”
Section: Discussionmentioning
confidence: 99%